Food and Fuel Prices : Recent Developments, Macroeconomic Impact, and Policy Responses. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This report provides a first broad assessment of the impact of the surge in food and fuel prices on the balance of payments, budgets, prices, and poverty of a large sample of countries. It reviews countries' macroeconomic policy responses to date and also discusses Fund advice for managing the price increases. Policies should (i) ensure that food and finance reaches the most affected countries as quickly as possible, (ii) include targeted and scaled-up social measures, and (iii) avoid high costs in terms of macroeconomic instability or loss in future agricultural production. Collaborating with international partners, the Fund also stands ready to provide balance of payments assistance. As the paper presents an initial assessment of a still-evolving situation, the somewhat tentative nature of the analysis should be borne in mind.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet